3D Segmentation of the Left Ventricle Combining Long- and Short-Axis MR Images - Säring, Dennis; Relan, J; Groth, M; Müllerleile, K; Heinz Handels (Methods of information in medicine, 2009)
OBJECTIVES: Segmentation of the left ventricle (LV) is required to quantify LV remodeling after myocardial infarction. Therefore spatiotemporal cine MR sequences including long-axis and short-axis images are acquired. In this paper a new segmentation method for fast and robust segmentation of the left ventricle is presented. METHODS: The new approach considers the position of the mitral valve and the apex as well as the long-axis contours to generate a 3D LV surface model. The segmentation result can be checked and adjusted in the short-axis images. Finally quantitative parameters were extracted. RESULTS: For evaluation the LV was segmented in eight datasets of the same subject by two medical experts using a contour drawing tool and the new segmentation tool. The results of both methods were compared concerning interaction time and intra- and inter-observer variance. The presented segmentation method proved to be fast. The mean difference and standard deviation of all parameters are decreased. In case of intra-observer comparison e.g. the mean ESV difference is reduced from 8.8% to 0.5%. CONCLUSION: A semi-automatic LV segmentation method has been developed that combines long- and short-axis views. Using the presented approach the intra- and interobserver difference as well as the time for the segmentation process are decreased. So the semi-automatic segmentation using long- and short-axis information proved to be fast and robust for the quantification of LV mass and volume properties.
Keywords: Heart Ventricles; Humans; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Magnetic Resonance Imaging, Cine; Mitral Valve; Myocardial Infarction; Observer Variation; Ventricular Remodeling